2015
DOI: 10.1002/jsfa.7150
|View full text |Cite
|
Sign up to set email alerts
|

A fermented sorghum/millet‐based beverage, Obiolor, extenuates high‐fat diet‐induced dyslipidaemia and redox imbalance in the livers of rats

Abstract: This study showed that Obiolor extenuated high-fat diet-mediated dyslipidaemia, protein oxidation, lipid peroxidation and DNA fragmentation in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…Lipid peroxidation, protein oxidation, and DNA fragmentation are consequential effects of overwhelmed antioxidant defense system. Elevated levels of lipid peroxidation products, CD, LH, and MDA, in this study are in accordance with previous studies [ 12 , 32 , 37 , 38 ]. This may lead to disorganization and functional loss of membrane [ 39 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Lipid peroxidation, protein oxidation, and DNA fragmentation are consequential effects of overwhelmed antioxidant defense system. Elevated levels of lipid peroxidation products, CD, LH, and MDA, in this study are in accordance with previous studies [ 12 , 32 , 37 , 38 ]. This may lead to disorganization and functional loss of membrane [ 39 ].…”
Section: Discussionsupporting
confidence: 94%
“…Oxidative stress associated with consumption of HFD results from overwhelmed antioxidant enzymes, which act in concerted manner to detoxify reactive oxygen species [ 34 ]. The decreased antioxidant enzymes observed in this study have been documented in HFD-fed rats [ 12 , 32 , 35 , 36 ]. Reversal of HFD-mediated decrease in these enzymes suggests antioxidant activity of the extract, although, in a different animal model, antioxidant activities of D. cumminsii have been reported [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Besides that, Queiroz et al [47] also demonstrated that a powdered drink mix made from sorghum flour which contained tannin showed significant antioxidant activity with a low calorific value. Another study by Ajiboye et al [43] on the effect of a non-alcoholic beverage (obiolor) produced from fermented sorghum and millet malts on the dyslipidemia, protein oxidation, lipid peroxidation, and DNA fragmentation in the liver of rats revealed a significant reduction in the DNA fragmentation, the peroxidation of lipids, protein oxidation, and dyslipidemia in the experimental rats. In addition, the production of a beverage such as tea from the black-colored sorghum variety with a high phenolic content showed a higher antioxidant activity compared to the white-colored variety of sorghum grains [44].…”
Section: Health Benefits Of Gluten-free Beveragesmentioning
confidence: 98%
“…Has potential for anti-hypertensive and anti-diabetic effects [42] Reducing effects of DNA fragmentation, peroxidation of lipids, and protein oxidation [43] High antioxidative properties [44] Kunnu with tigernut extract has enhanced antioxidative potentials [45] Addition of lactic acid bacteria to beverage made from sorghum and amaranth composites displayed an increased digestibility of protein, increased bio-accessibility of zinc and iron and a higher availability of lysine [46] Powdered drink mix Has antioxidant properties and is low in calories [47] 2.2.1. Health Benefits of Gluten-Free Bread, Pasta, Cookies, and Crackers…”
Section: Breadmentioning
confidence: 99%